Faktor Yang Memengaruhi Kepatuhan Kunjungan Antenatal Care (ANC) Era Covid 19 di Klinik Madina Tahun 2022 - Nurrahmaton Nurrahmaton; Pratiwi Nasution; Bella Santika (Jurusan Kebidanan Poltekkes Kemenkes Padang, 2023)
The Covid-19 pandemic has greatly changed the status of daily life around the world and for working from home via the internet. WHO in 2019 stated that the maternal mortality rate in the world was 830/100,000 live births. The purpose of this study was to determine the factors that influence compliance with ANC visits in the Covid-19 era at the Madina clinic in 2022. The research design used in this study was an analytic survey with a cross-sectional approach. The population in this study were third trimester pregnant women as many as 36 respondents. The sample uses a Total Population of 36 people. Data analysis techniques used Univariate and Bivariate Analysis. The results showed that there was an effect between knowledge and ANC visit compliance with statistical test results obtained p-value = 0.003, there was an effect between attitudes towards ANC visit compliance p-value = 0.009, there was an effect between employment status on adherence to ANC visits p-value = 0.021, and there is an effect between the support of health workers on compliance with ANC visits p-value = 0.011 Conclusion: There is a significant influence between knowledge, attitudes, employment status and support of health workers on adherence to ANC visits at the Madina clinic in 2022 It is hoped that the health workers at the Madina clinic will play an active role in ANC services